2020
DOI: 10.1017/dsd.2020.27
|View full text |Cite
|
Sign up to set email alerts
|

Risk Management in Product Development: Risk Identification, Assessment, and Mitigation – A Literature Review

Abstract: This paper reviews the literature on risk management practices and methods in product design and development. Based on an expert workshop by the Risk Management Processes and Methods in Design Special Interest Group within the Design Society and literature review, three key areas are discussed: risk identification, assessment, and mitigation. In each area, researchers have described practices that are used in product development organizations, proposed new methods to support risk management processes and decis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…As human beings enter the 21st century, the world has entered the era of informationization. Under the influence of the general trend, my country's e-commerce is also developing by leaps and bounds [4][5][6]. According to the survey report of the National Bureau of Statistics, from January to March 2015, the sales of all online goods and services in China reached 760.7 billion yuan, a year-on-year increase of 41.300 yuan.…”
Section: Introductionmentioning
confidence: 99%
“…As human beings enter the 21st century, the world has entered the era of informationization. Under the influence of the general trend, my country's e-commerce is also developing by leaps and bounds [4][5][6]. According to the survey report of the National Bureau of Statistics, from January to March 2015, the sales of all online goods and services in China reached 760.7 billion yuan, a year-on-year increase of 41.300 yuan.…”
Section: Introductionmentioning
confidence: 99%
“…An effective and efficient risk management strategy must be selected to match the specific product development case. Firms that develop products use risk identification, assessment, and mitigation to support their risk management procedures and decision-making [25], where the risks are detectable and manageable. Product development industries are also assisted in incorporating sustainability into strategic, tactical, and operational decision-making [26].…”
Section: Literature Reviewmentioning
confidence: 99%
“…In this section, it is examined how project-, team-, and riskrelated management may affect coordination needs and whether it has been indicated that characteristics influence the performance of teams. [1] conducted a literature review on risk management practices and methods in the design and development of products. The mentioned study also investigated the types of evidence utilized to assess the efficiency of risk management activities.…”
Section: Related Workmentioning
confidence: 99%